A clockwise P‐T‐t-D path of the northern Patagonia basement: Implications for the Permian evolution of the Panthalassan margin of Gondwana. - González, Pablo Diego (2024)
Fil: González, Pablo Diego. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología, Río Negro, Argentina